Dual Improvement of β‐MnO2 Oxygen Evolution Electrocatalysts via Combined Substrate Control and Surface Engineering. Issue 23 (18th September 2020) - Bigiani, Lorenzo; Gasparotto, Alberto; Maccato, Chiara; Sada, Cinzia; Verbeeck, Johan; Andreu, Teresa; Morante, Juan Ramón; Barreca, Davide
Abstract: The development of catalysts with high intrinsic activity towards the oxygen evolution reaction (OER) plays a critical role in sustainable energy conversion and storage. Herein, we report on the development of efficient (photo)electrocatalysts based on functionalized MnO2 systems. Specifically, β ‐MnO2 nanostructures grown by plasma enhanced‐chemical vapor deposition on fluorine‐doped tin oxide (FTO) or Ni foams were decorated with Co3 O4 or Fe2 O3 nanoparticles by radio frequency sputtering. Upon functionalization, FTO‐supported materials yielded a performance increase with respect to bare MnO2, with current densities at 1.65 V vs . the reversible hydrogen electrode (RHE) up to 3.0 and 3.5 mA/cm 2 in the dark and under simulated sunlight, respectively. On the other hand, the use of highly porous and conductive Ni foam substrates enabled to maximize cooperative interfacial effects between catalyst components. The best performing Fe2 O3 /MnO2 system provided a current density of 17.9 mA/cm 2 at 1.65 V vs . RHE, an overpotential as low as 390 mV, and a Tafel slope of 69 mV/decade under dark conditions, comparing favorably with IrO2 and RuO2 benchmarks. Overall, the control of β ‐MnO2 /substrate interactions and the simultaneous surface property engineering pave the way to an efficient energy generation from abundant natural resources. Abstract : β ‐MnO2 nanostructures, eventually decorated with Co3 O4 or Fe2 O3 nanoparticles, are grown by a plasma‐assisted strategy on conductive glasses and porous Ni foams, and investigated as catalysts for the oxygen evolution reaction. The combined control over substrate properties and β ‐MnO2 surface decoration yields outstanding functional performances, paving the way to real‐world applications in sustainable energy conversion processes.